UNDERSTANDING GEOMETRIC PROGRESSIONS: A BASIC MATHEMATICAL CONCEPT JURAYEV MUZAFFARJON MANSURJONOVICH - Nuritdinova Umida Muhammedali (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, a general analysis of theoretically based approaches to the identification of effective methods and tools, which are important for teaching rectangles and their properties in general education schools, and the use of methodologies for teaching the subject of rectangles is described.